Improving blast disease tolerance in rice plants by enhancing antioxidant defense with tebuconazole and trifloxystrobin fungicides - Ferdousi, Mahfuza; Tran, Quang Dan; Aminuzzaman, F. M.; Islam, Md. Rafiqul; Chowdhury, M. Salahuddin M.; Hasan, Amit; Jerin, Jafrin Jahan; Shompa, Bodrun Nessa; Fujita, Masayuki; Mohsin, Sayed Mohammad (Hue University Journal of Science: Natural Science, 2025)
The fungus Magnaporthe oryzae (Mo) is the causal agent of rice blast disease, one of the most common and serious diseases affecting cultivated rice. Developing effective techniques to manage this disease is currently a crucial issue. Therefore, this study was designed to investigate the protective role of two fungicides, tebuconazole (TEB) and trifloxystrobin (TRI), in enhancing the tolerance of rice seedlings to blast disease. Ten-day-old hydroponically grown seedlings were inoculated with a Mo spore suspension, and after three days, fungicide was sprayed. In 15-day-old seedlings, numerous blast symptoms were observed, which hindered their growth. Compared with the control, Mo inoculation increased the malondialdehyde (MDA) and hydrogen peroxide (H2O2) content by 249.37 and 118.29%, respectively. In addition, Mo inoculation also increased electrolyte leakage (EL) in both shoots and roots and caused a reduction in leaf relative water and photosynthetic pigment contents. However, exogenous application of TEB and TRI reduced the content of MDA, H2O2, and EL. Fungicide application also increased Chl a, Chl b, Chl (a+b), and the carotenoid content by 28.16, 41.61, 33.67, and 26.29%, respectively. Consequently, increased photosynthetic pigment and relative water contents, along with increased rice seedling biomass and growth, were observed. These findings suggest that exogenous administration of TEB and TRI is a promising technique for improving blast tolerance in rice plants.